1992
DOI: 10.3168/jds.s0022-0302(92)78040-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pearl Millet and Field Peas Plus Triticale Silages for Midlactation Dairy Cows

Abstract: A mixture of field peas and triticale was planted in spring, harvested as silage, and followed by a double crop of pearl millet, which also was harvested as silage. Eighteen Holstein cows were fed diets based on pea with triticale, pearl millet, or alfalfa plus corn silages. Dry matter digestibility of the pea with triticale diet was higher than for control (71.1 vs. 66.9%), but DM digestibility was not different between control and pearl millet diets. Milk production was not affected by diets containing pea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
6
19
2
1
Order By: Relevance
“…No differences in feed intake were observed between individual experimental groups or between experimental groups and control group. VALENTINE and BARTSCH (1987) and MESSMAN et al (1992) reported a positive effect of peas on the overall intake of dry mass in dairy cows; similar results were found by REED et al (2004) in bulls. LOSAND et al (2003) recommend feeding no more than 4,0 kg of peas per day and one dairy cow.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…No differences in feed intake were observed between individual experimental groups or between experimental groups and control group. VALENTINE and BARTSCH (1987) and MESSMAN et al (1992) reported a positive effect of peas on the overall intake of dry mass in dairy cows; similar results were found by REED et al (2004) in bulls. LOSAND et al (2003) recommend feeding no more than 4,0 kg of peas per day and one dairy cow.…”
Section: Methodssupporting
confidence: 72%
“…Other researchers (CORBETT et al, 1995;MESSMAN et al, 1992) have reported increased concentrations of milk fat in cows fed the peas during all lactation stages compared to cows fed the soya. They believe that higher milk fat levels are caused by complex, non-structural, low-degradable saccharides contained in peas.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…However, Adewakun et al (1989) reported that NDF digestibility remained significantly unaltered between maize and sorghum silages. Messman et al (1992) reported that the NDF contents of millet silage were less digestible than that of corn silage plus alfalfa silage-based diet because of higher lignification. However, in the present study, maize silage had less lignin contents than millet silage due to which NDF digestibility value of maize silage was higher.…”
Section: Neutral Detergent Fibre Digestibilitymentioning
confidence: 97%
“…Because of its adaptability to harsh conditions, millet can be grown in areas that are unfavorable to other crops such as maize (Singh and Singh, 1995). Although, several studies have evaluated the potential of pearl millet as forage for ruminants in dry regions (Messman et al, 1992; Hill et al, 1999), data on its management are limited, especially about ideal sowing dates. For semi-arid regions, the planting date decision is important not only because of its effect on yield but also the need to minimize the risk of establishment failures and to decrease cost and labor required for replanting.…”
Section: Introductionmentioning
confidence: 99%